Development of a fixed-dose combination capsule of carbamazepine and gabapentin - Irda Haslinda binti Hassan (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2018)
The rate of patient's compliance is markedly reduced as the number of medications and dosing frequency increased. The compliance for the combination of carbamazepine tablet which is twice daily dosing and gabapentin capsule which is given three times daily is greatly affected in painful diabetic peripheral neuropathy patient. This study aim to develop a fixed-dose combination of carbamazepine and gabapentin (FDC CBZ-GBP) in order to simplify the treatment and improve the compliance. Hence, it is important to identify the compatible excipient for both drugs for the purpose of formulation development. Compatibility study was performed on both active pharmaceutical ingredients (API) and each API with several excipients using differential scanning calorimetry (DSC) and supported by attenuated total reflectance-fourier transform infrared spectroscopy (ATR-FTIR). DSC results showed incompatibility between GBP and CBZ, lactose monohydrate, magnesium stearate, talc and hydroxylpropyl methylcellulose where the melting peak of GBP significantly shifted. However, ATR spectra of those combinations excluded these incompatibilities. Preliminary lab scale production of FDC CBZ-GBP for 2 kilograms was done with the incorporation of 2 excipients only; namely, lactose and magnesium stearate. The lab scale FDC CBZ-GBP had flow function > 10, compressibility index 11.73±2.28% and Hausner ratio 1.13 ± 0.03 which indicated free-flowing powder. Thus, the intended fill weight of 300 mg ± 7.5% can be achieved. The analytical method development (AMD) and analytical method validation (AMV) of FDC CBZ-GBP including specificity, accuracy, precision, intermediate precision, linearity, limit of detection (LOD) and limit of quantification (LOQ) were performed by using HPLC. All the AMV parameters met all the compendial specifications. FDC CBZ-GBP was scaled-up to 24 kilograms to identify optimum processing parameters such as mixing time, mixing direction, dosator speed and dose controller. Based on scale-up results, the optimum mixing time was 52.5 min with 4 clockwise and 2 anticlockwise turns. The expected setting of dosator speed (400 pcs/min) and dose controller (15 mm) for capsule filling process was not stable because process capability index (Cpk) was less than 1. Samples from scale-up process were taken and stored in both real time and accelerated stability chambers for stability study. All stability study parameters including moisture content, assay of carbamazepine and gabapentin, disintegration time and dissolution profile at all-time points met the compendial specifications. In conclusion, FDC CBZ-GBP was successfully developed into a new dosage form of a fixed-dose capsule.